Pediatric Clinical Pharmacology Studies in Chagas Disease - Garcia Bournissen, Facundo (2009)
Chagas disease is a neglected parasitic disease endemic in the Americas. It mainly affects impoverished populations and the acute phase of the infection mostly affects children. Many cases have also been detected in nonendemic countries as a result of recent migratory trends. The chronic phase is relatively asymptomatic, but 30% of patients with chronic infection eventually develop cardiac and digestive complications that commonly lead to death or disability. Only two drugs are available for the treatment of Chagas disease, benznidazole and nifurtimox. These drugs have been shown to be effective in the treatment of both acute and early chronic phases in children, but the pharmacokinetics of these drugs have never been studied in this population. We have set out to conduct a pharmacokinetics study of benznidazole in a pediatric population with Chagas disease. The results of this study are expected to allow better estimation of the optimal doses and schedule of pharmacotherapy for Chagas disease in children.